Board composition, CEO duality and firm performance: Malaysian plantation sector - Ong, Tze San; Lee, Soon Yau (Universiti Putra Malaysia Press, 2013)
This paper seeks to examine the roles of independent members on the board and CEO duality on firm performance in Malaysia. Data on 40 Malaysian plantation companies over 2007 and 2010 are used. The result shows that independent directors may not fully understand the operations of their firms since they might not be fully involved in business activities. The findings indicate that a dual leadership structure is more effective with larger board sizes and longer years of operation. In the context of Malaysian plantations, firms should balance their number of outsiders and adopt a CEO duality structure in order to be competitive in facing external threats.